2019
DOI: 10.3390/e21050474
|View full text |Cite
|
Sign up to set email alerts
|

Processing and Characterization of Refractory Quaternary and Quinary High-Entropy Carbide Composite

Abstract: Quaternary high-entropy ceramic (HEC) composite was synthesized from HfC, Mo2C, TaC, and TiC in pulsed current processing. A high-entropy solid solution that contained all principal elements along with a minor amount of a Ta-rich phase was observed in the microstructure. The high entropy phase and Ta-rich phase displayed a face-centered cubic (FCC) crystal structure with similar lattice parameters, suggesting that TaC acted as a solvent carbide during phase evolution. The addition of B4C to the quaternary carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 23 publications
3
17
0
Order By: Relevance
“…The strongest diffraction peak of the hexagonal (191) structure at 2θ = 44° (marked with the red arrow) started to be visible at 1800 °C, suggesting the initial formation of hexagonal phase at 1800 °C. The composition of HEC-(SiC)x composites at 2000 °C is similar to what was achieved in our previous study on the B4(HfMo2TaTi)C/SiC composite, however at lower temperature (1800 °C) [17], attributed to a higher heating rate applied in this study (200 °C/min compare to 100 °C/min). Similar dependence of the sintering temperature on the heating rate in SPS has been reported [52,53].…”
Section: Sic Effect On Phase Fractionsupporting
confidence: 88%
See 3 more Smart Citations
“…The strongest diffraction peak of the hexagonal (191) structure at 2θ = 44° (marked with the red arrow) started to be visible at 1800 °C, suggesting the initial formation of hexagonal phase at 1800 °C. The composition of HEC-(SiC)x composites at 2000 °C is similar to what was achieved in our previous study on the B4(HfMo2TaTi)C/SiC composite, however at lower temperature (1800 °C) [17], attributed to a higher heating rate applied in this study (200 °C/min compare to 100 °C/min). Similar dependence of the sintering temperature on the heating rate in SPS has been reported [52,53].…”
Section: Sic Effect On Phase Fractionsupporting
confidence: 88%
“…The hexagonal (191) phase shows lattice parameters of a = 0.3051 nm and c = 0.3237 nm, while the FCC phase in all composites shows a lattice constant of approximately 0.447 nm, which is close to the lattice parameter of the constituent metal carbides TaC (0.446 nm, ICDD 03-065-8792, 50.3 at% C). The phase formation mechanism discussed in our previous work on high-entropy boron-carbides [16,17] suggested that TaC was the host FCC lattice in the current carbide system so that other atoms migrate in and occupy the corresponding cationic and anionic sites in the TaC rocksalt structure, due to the lowest metal vacancy formation energy of TaC among the FCC carbides.…”
Section: Sic Effect On Phase Fractionmentioning
confidence: 91%
See 2 more Smart Citations
“…The development and preparation of composites have realized the complementary advantages of a variety of different component materials, which can further improve the overall performance of alloys. Zhang et al [ 39 ] prepared a high-entropy ceramic composite by using HfC, Mo 2 C, TaC, and TiC in pulsed-current processing. Furthermore, Li et al [ 40 ] used a mixture of carbides and oxides in the preparation of an NbMoCrTiAl HEA.…”
Section: Mechanical Behaviorsmentioning
confidence: 99%